The Correlation of Metacognition with Critical Thinking Skills of Grade XI Students on Human Excretion System Concept - Diella, Dea; Ardiansyah, Ryan (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2017)
Abstract The aims of this study is to reveal metacognition and critical thinking skill of students grade XI, and also the correlation between metacognition with crititical thinking skill on human excretion system. The participants of this study consist of 100 students from grade XI of five different high schools in Tasikmalaya. Correlational method was used in this study. Instruments which used to obtain the data consist of metacognition test and critical thinking test. The students' metacognition was captured with the essay item related to the human excretion system concept. The multiple choice-reason item and essay item was used to capture the critical thinking skills. The results showed that students’ score at metacognition and critical thinking have a low average. The results also proved that metacognition has a positive correlation and moderately strong with critical thinking skills. Keywords: Metacognition, Critical Thinking Skills, Human Excretion System